Accountability for the Use of State Property: Criticism Based on the HAMKA’s Amanah Perspective - Akmaldiya, Akmaldiya; Tarmizi, M. Irfan; Birton, M. Nur A (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to criticize the accountability of the implementation of the Determination of Use Status (PSP) of State Property (BMN) at the Ministry of Religious Affairs. The research approach uses a qualitative approach. Data sources come from documentation and in-depth interviews with BMN Managers. The data analysis technique uses the Miles and Huberman approach modified with critical reflection from Amanah HAMKA’s perspective, including reduction, presentation, and verification based on Amanah HAMKA’s perspective in the form of trustworthiness and professionalism. The research results found that BMN management was hampered by several things, namely: (1) professionalism of human resources; (2) limited budget; (3) inaccurate information; (4) unclear duties and functions regulations; (5) low level of leadership concern; (6) low coordination; (7) inadequate internal supervision; and (8) unclear performance targets. In conclusion, the implementation of PSP at the Ministry of Religious Affairs reflects a failure in carrying out Amanah, which, according to HAMKA means being trustworthy and demanding responsibility and integrity. HAMKA emphasizes the importance of fulfilling the mandate to its experts. The principle of trust has not become the main guideline, resulting in a decline in the quality of BMN management. This research is an effort to criticize conventional egoistic and materialistic accountability. It emphasizes a holistic and spiritual accountability approach according to the HAMKA mandate perspective, focusing on trustworthiness and professionalism.